Judicial precedent as a dynamic rationale for axiomatic bargaining theory - Marc Fleurbaey; John E. Roemer (Theoretical Economics, 2011)
Axiomatic bargaining theory (e.g., Nash's theorem) is static. We attempt to provide a dynamic justification for the theory. Suppose a Judge or Arbitrator must allocate utility in an (infinite) sequence of two-person problems; at each date, the Judge is presented with a utility possibility set in the nonnegative orthant in two-dimensional Euclidean space. He/she must choose an allocation in the set, constrained only by Nash's axioms, in the sense that a penalty is paid if and only if a utility allocation is chosen at date T which is inconsistent, according to one of the axioms, with a utility allocation chosen at some earlier date. Penalties are discounted with t, and the Judge chooses any allocation, at a given date, that minimizes the penalty he/she pays at that date. Under what conditions will the Judge's chosen allocations converge to the Nash allocation over time? We answer this question for three canonical axiomatic bargaining solutions: Nash's, Kalai-Smorodinsky's, and the 'egalitarian' solution, and generalize the analysis to a broad class of axiomatic models.
Keywords: C70; C78; K4; 330; Axiomatic bargaining theory; judicial precedent; dynamic foundations; Nash's bargaining solution